Sebuah Tinjauan Sistematis Bunga Telang (Clitoria ternatea L.) untuk Menurunkan Berat Badan dan Memperbaiki Profil Lipid pada Mencit dan Tikus dengan Obesitas : Bunga Telang untuk Memperbaiki Berat Badan dan Profil Lipid - Fista Utami; Dono Indarto; Shanti Listyawati; Alfian Abdul Rajab (Universitas Airlangga, 2023)
Background: Butterfly pea flowers (Clitoria ternatea L.) are edible plants found in Asian countries that have several phytochemical compounds thathave potential anti-obesity and anti-dyslipidemia. From several in vivo studies, the administration of various extracts of butterfly pea flowers has different effects to reduce body weight (BW) or body mass index (BMI), and lipid profiles. Objectives: To analyze systematically the effects of butterfly pea flowers on BW or BMI and lipid profiles in rodents with or without obesity. Methods: This study used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and bias risk using the Systematic Review Centre for Laboratory Animal Experimentation (SyRCLEs).Original articles were from Google Scholar, PubMed, ResearchGate, and Science-Direct with criteria: randomized control trial (RCT), published from 2019 to 2023, rodents, and research outcomes (BW and lipid profiles). Results: Four original articles met the research criteria. Giving 1,000 mg/kg BW of the aqueous extract of butterfly pea flower for seven days reduced BW. Another study reported that giving 130 mg/kg BW butterfly pea flowers kombucha inhibited weight gain. Doses of 0.25 and 0.50% of the aqueous extracts of butterfly pea flowers for 15 weeks did not affect BW butthe dose of 2% prevented weight gain. Conclusions: Butterfly pea flowers have beneficial effects on reducing BW and improving lipid profiles in rodents with severaldiets although vary in animal models, diet types, extraction methods, and research design. This study becomes important evidence for further study.